2022
DOI: 10.3390/jpm12081280
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Dental Age Estimation: Development of New Algorithm Based on the Minimal Necessary Databases

Abstract: Objectives Dental age determination relies on the presence of wisdom teeth, which can be assigned to specific age ranges according to their stage of development. The purpose of this study is to highlight the applicability of the Demirjian staging of layman compared to expert, as well as the inclusion of all four wisdom teeth in the overall assessment, in order to emphasize and critically highlight a precise age estimation in clinical practice, especially in the case of agenesis or the presence of less than all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The wisdom tooth used, which tends to be preferred here, should be either tooth 38 or 48. This was already shown in a previous study by the working group [ 42 ] and is consistent with other literature [ 58 ]. A study by Bassed et al also demonstrated the importance of clavicle and wisdom tooth cooccurrence for age determination in a population study of 600 deceased individuals in Australia [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The wisdom tooth used, which tends to be preferred here, should be either tooth 38 or 48. This was already shown in a previous study by the working group [ 42 ] and is consistent with other literature [ 58 ]. A study by Bassed et al also demonstrated the importance of clavicle and wisdom tooth cooccurrence for age determination in a population study of 600 deceased individuals in Australia [ 20 ].…”
Section: Discussionsupporting
confidence: 94%
“…Thus, the indication is patient-specific and does not always involve all four wisdom teeth of an individual at the same time. If all four wisdom teeth are discoverable, the literature indicates greater accuracy in the mandible’s wisdom teeth related to the biological age than in the wisdom teeth of the upper jaw [ 41 , 42 ]. Often the maxillary wisdom teeth are not located in this context due to reduced image quality, and a study by Bjelopavlovic et al showed that the combination of tooth 38 and another, preferably tooth 48, would show the most accurate results in terms of dental age diagnosis [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral age is calculated as an objectively measurable oral health index and is a biological age that reflects oral health status. Oral age reflects the development of modern medicine and lifestyle changes and can be considered a concept related to biological age that can be compared based on the average oral health status of an entire nation [ 27 , 28 ]. It is an age estimation method that is widely used to estimate an accurate age.…”
Section: Discussionmentioning
confidence: 99%
“…Simple and multiple linear regressions were used to obtain a parsimonious model, allowing estimation of chronological age from the measurements made of the seven teeth based on each method and the variables of sex and age group, since in previous studies the Demirjian method is shown to be sensitive to these variables [7,30,[35][36][37][38]. Using regression equations provides a more precise approach to chronological age based on Demirjian's staging method [43]. The statistical assumptions of the models were analyzed and fulfilled, namely those of normal distribution, homogeneity, and independence of errors.…”
Section: Ethics Procedures and Data Analysismentioning
confidence: 99%